2022
DOI: 10.1101/2022.08.26.505326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network of mixed actin polarity in the leading edge of spreading cells

Abstract: Physical interactions of cells with the underlying extracellular matrix (ECM) play key roles in multiple cellular processes, such as tissue morphogenesis, cell motility, wound healing, cancer invasion and metastasis. The actin cytoskeletal network is a central driver and regulator of cellular dynamics, that produces membrane protrusions such as lamellipodia and filopodia. In this study, we examined actin organization in the expanding lamellipodia during the early stages of cell spreading. To gain insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…We observed that the second-color actin was incorporated into the pillar from the bottom but not from the side or top, indicating that the barbed ends of actin filaments just polymerized and not yet capped with CPs were localized near the VVCA area and pointed toward the bilayer, as observed in lamellipodia of motile cells. 38 This result suggests that the addition of new actin monomers to the barbed ends generates pushing forces to grow actin pillars perpendicularly from the bilayer. Collectively, the system can spatially constrain actin nucleation on a lipid bilayer and assemble micrometer-sized actin networks, mimicking the molecular dynamics of lamellipodia in terms of recapturing both the lateral diffusion of NPFs and the polarized growth of actin networks toward the NPF areas on the plasma membrane.…”
mentioning
confidence: 95%
“…We observed that the second-color actin was incorporated into the pillar from the bottom but not from the side or top, indicating that the barbed ends of actin filaments just polymerized and not yet capped with CPs were localized near the VVCA area and pointed toward the bilayer, as observed in lamellipodia of motile cells. 38 This result suggests that the addition of new actin monomers to the barbed ends generates pushing forces to grow actin pillars perpendicularly from the bilayer. Collectively, the system can spatially constrain actin nucleation on a lipid bilayer and assemble micrometer-sized actin networks, mimicking the molecular dynamics of lamellipodia in terms of recapturing both the lateral diffusion of NPFs and the polarized growth of actin networks toward the NPF areas on the plasma membrane.…”
mentioning
confidence: 95%